Епідеміологія та природний перебіг гепатиту С - Голубовська, О. А. (Clinical Endocrinology and Endocrine Surgery, 2008)
On the basis of our research and literature data is shoun that HCV predominantly courses in chronic form without acute phase. Disease has a lot of extrahepatic manifestations which don’t influence on its progress in liver but affect life quolity of patients. They are predictors of unfavourable reaction on antiviral therapy. Coinfection with HBV may lead to elimination of hepatitis virus B and C in blood due to interference effect.